2006
DOI: 10.2460/javma.228.7.1063
|View full text |Cite
|
Sign up to set email alerts
|

Clinical signs and clinicopathologic abnormalities in dogs with clinical spirocercosis: 39 cases (1996–2004)

Abstract: Results suggest that clinical spirocercosis occurs more often in young-adult, large-breed dogs. Nonregenerative anemia, neutrophilic leukocytosis, hyperproteinemia, and high alkaline phosphatase activity may be useful clinicopathologic indicators of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The finding of pockets of neutrophils within nodules has been described, but not the high prevalence and severity of the lymphoplasmacytic infiltrate. Interestingly, in a previous study, 8% of spirocercosis cases showed lymphocytosis in their complete blood count (Mylonakis et al, 2006). Lympho-plasmacytic inflammation has been described in association with Helicobacter-induced gastritis, where T helper lymphocyte type 1 (Th1) cells and their associated cytokines are thought to play a significant role in carcinogenesis (Wilson and Crabtree, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of pockets of neutrophils within nodules has been described, but not the high prevalence and severity of the lymphoplasmacytic infiltrate. Interestingly, in a previous study, 8% of spirocercosis cases showed lymphocytosis in their complete blood count (Mylonakis et al, 2006). Lympho-plasmacytic inflammation has been described in association with Helicobacter-induced gastritis, where T helper lymphocyte type 1 (Th1) cells and their associated cytokines are thought to play a significant role in carcinogenesis (Wilson and Crabtree, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, esophageal masses may result in dysphagia and, particularly those involving the thoracic esophagus can be identified radiographically. Spirocerca lupi is a nematode that infests the canine esophagus resulting in radiographically apparent esophageal masses, caudal thoracic vertebral spondylitis, and aortic undulation [15, 16]. Transformation of Spirocerca granulomas into malignant sarcomas has been reported and also results in radiographically visible esophageal masses [17, 18].…”
Section: Radiographymentioning
confidence: 99%
“…Our dog was negative for S. lupi eggs after having employed the fecal sedimentation technique. On thoracic radiographs, the characteristic finding of canine spirocercosis is an accumulation of intraluminal air and not the diffuse esophageal dilation that is typically seen in megaesophagus cases (Dvir et al 2001, Mylonakis et al 2006). Similar to our case, as high as 88.7% of the dogs with either localized or generalized MG have been into spontaneous serologic and clinical remission on an average of 6.4 months after diagnosis (range: 1-18 months) (Shelton 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Canine spirocercosis is a relatively common cause of esophageal dysphagia and regurgitations, especially among hunting breed dogs living in Greece (Mylonakis et al 2006). Our dog was negative for S. lupi eggs after having employed the fecal sedimentation technique.…”
Section: Discussionmentioning
confidence: 99%